P260 PRELIMINARY EXPERIENCE OF REPEATED LEVOSIMENDAN INFUSIONS IN ELDERLY OUTPATIENTS WITH ADVANCED HEART FAILURE. (18th May 2022) - Camartini, V; Orso, F; Herbst, A; Virciglio, S; Salucci, C; Verga, F; D'Errico, G; Di Bari, M; Ungar, A; Fattirolli, F; Marchionni, N; Baldasseroni, S
Abstract: Background: The use of intermittent infusion of Levosimendan (L) demonstrated to be able to reduce hospitalisations and to improve functional capacity and quality of life in patients with advanced heart failure (HF). Purpose: To describe our preliminary experience regarding L intermittent infusions in advanced HF older outpatients. Methods: A maximum of three consecutive L infusions were carried out 14 days apart. The duration of each session was 8 hours. The starting infusion rate was 0.05 μg/Kg/min, titrated every 30/60' up to a maximum of 0.2 μg/Kg/min based on blood pressure, heart rate and arrhythmias recorded during telemetry. We evaluated patients by clinical, laboratory and echocardiographic controls at baseline and two weeks after the end of treatment. Results: Since November 2020 we enrolled 17 patients with a mean age of 77 years; 12% were women. HF etiology was ischemic in 64% of cases and the mean ejection fraction was 30%. A total of 41 infusions were performed, the mean dose of L administered was 5.4 mg/infusion. Three patients did not complete the expected treatment, one due to an intercurrent COVID–19 infection and two because of social issues. In 28 sessions the maximum infusion rate was reached, while in 12 a lower rate; in one case drug infusion was suspended (Figure 1 ). The main complication observed was marked non–symptomatic hypotension, followed by the onset of atrial fibrillation or frequently ventricular extrasystole. As shown in Figure 2, at the end of the infusion cycles, there was an improvement of clinical and hemodynamic parameters. Moreover, at the end of the infusion cycles, we observed a reduction in the mean dose of loop diuretic prescribed and an increase in the prescription of disease–modify treatment, according to HF guidelines (Figure 3 ). Conclusions: In our preliminary experience repeated infusions of L appear to be well tolerated in older patients with advanced HF. Although there was an improvement in congestion parameters and targeted therapy for HF, more data will be needed in the future to confirm its safety and efficacy, also in terms of guidelines–directed medical therapy.